Transportation model for the distribution of cocoa in Mexico - Rivera López, Samuel; Gutiérrez Hernández Maricruz; Pérez Soto Francisco (Revista Mexicana de Ciencias Agrícolas, 2019)
Cocoa is a product originating in Mexico whose production does not meet domestic demand, so there is a need to import much of what the Mexican market consumes, therefore, it is of great importance to distribute optimally the quantities produced internally with the purpose of minimizing the transportation costs of the grain. The objective of the research was to formulate a transport model that optimizes the distribution of cocoa in Mexico, minimizing the cost of transportation, both for a closed economy and for an open economy. Linear programming was used to solve the transport problem, since it allows determining the optimal way to transfer goods, minimizing total distribution costs. The main results show that the national apparent consumption, in 2015, was 51 394.13 t, the apparent per capita consumption of cocoa in the country was 0.43 kg. The states that can see totally satisfied their demand for cocoa, only with the surplus of state production of Tabasco and Chiapas, are: Guerrero, Oaxaca, Querétaro, Quintana Roo, Tamaulipas, Veracruz, Campeche, Mexico City, Hidalgo, State of Mexico, Morelos, Puebla, Tlaxcala and Yucatán, while Michoacán can obtain 14 of the 65 trucks it demands. The above, leads to a minimization of transportation costs, this being 9 500 068.00. In order to meet the national demand for cocoa, two ports of entry for this crop were considered and the minimum transportation cost was 18 123 640.00.